«Uncanny valley» effect in holographic image transmission - Shoydin, Sergey A.; Pazoev, Artem L. (Journal of the Belarusian State University. Physics, 2022)
The quality of computer-synthesised images is continuously improving, increasing in the volume of files representing them. It is noticed that passing from simple schematic images to increasingly complex ones, their perception goes through different stages. If initially the complication of the image and its approximation to the real image of a person makes a favourable impression, then there comes a moment of fright and rejection. Masahiro Mori called it the «uncanny valley» effect. Since then, all new technologies for presenting human images have been tested in order to avoid this effect. This effect should be treated especially carefully when compressing and then restoring complex images. This paper shows the position relative to the «uncanny valley» of the reconstructed 3D images, reconstructed by a hologram synthesised and transmitted with compression over the communication channel in accordance with patent RU2707582C1.